Strengthening Pancasila Student Profiles In Independent Learning Curriculum In Elementary School - Nurhayati; Jamaris; Sufyarma Marsidin (CV. AFDIFAL MAJU BERKAH, 2022)
The objective of this study is to see how the Pancasila Student Profile is strengthened in the Independent Learning Curriculum in elementary schools. The data collection method was the research library, and the approach was qualitative. According to the findings of the study, reinforcing the Pancasila Student Profile in the Independent Learning Curriculum provides a solution for developing Pancasila-based character. The Pancasila Student Profile has six competencies consisting of faith, fear of God Almighty, noble character, global diversity, cooperation, independence, critical reasoning, and creativity. The Pancasila Profile strengthening project is cross-disciplinary learning with a Project-Based learning approach and differs from project-based learning in the classroom. The government is promoting the Transformational Teacher Program as the spearhead of equal distribution of education and strengthening the Pancasila Student Profile. The government assists transformational schools through consultative and asymmetric assistance, strengthening school human resources, learning with a new paradigm, data-based planning, and digitizing schools